Field Identification of Citrus Blight - Stephen H. Futch; Kenneth S. Derrick; Ronald H. Brlansky (EDIS, 2005)
Citrus blight is a disease that causes thousands of trees to become unproductive every year, resulting in losses in excess of $60 million annually. The cause of blight is unknown. The disease is found in many citrus-producing regions including North America, the Caribbean, South America, South Africa and Australia. Blight is found in mostly tropical or semitropical regions with moderate to heavy rainfall but is not reported in more arid regions such as the Mediterranean Basin and California. Blight has been present in Florida for more than 100 years and was frequently called young tree decline in the 1960s and 70s. This document is HS995, one of a series of the Horticultural Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published February 2005.